2021
DOI: 10.3389/fonc.2021.724432
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Extrathyroidal Extension Results in Increased Rate of Tumor Recurrence and Is an Independent Predictor of Patient’s Outcome in Middle Eastern Papillary Thyroid Carcinoma

Abstract: BackgroundPapillary Thyroid Cancer (PTC) is the most common endocrine malignancy, with recurrence rate as high as 30%. A great deal of controversy surrounds the significance of microscopic extrathyroidal extension (m-ETE) as a prognostic factor. The most recent edition (8th) of American Joint Committee on Cancer (AJCC) staging system has removed m-ETE from the definition of pT3, which suggests that m-ETE may lack prognostic impact in PTC patients. Moreover, data about m-ETE prevalence and clinical impact on Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Gross ETE was recognized as a variable that negatively affects prognosis in DTC, and whether microscopic ETE significantly increases the risk of recurrence and overall mortality remains controversial ( 33 35 ). A recent study has reported that microscopic ETE was an independent predictor of recurrence-free survival and significantly associated with poor survival ( 36 ). Another study reached the opposite conclusion that microscopic ETE had no effect on the risk of death or recurrence ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gross ETE was recognized as a variable that negatively affects prognosis in DTC, and whether microscopic ETE significantly increases the risk of recurrence and overall mortality remains controversial ( 33 35 ). A recent study has reported that microscopic ETE was an independent predictor of recurrence-free survival and significantly associated with poor survival ( 36 ). Another study reached the opposite conclusion that microscopic ETE had no effect on the risk of death or recurrence ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jingzhe Xiang et al found that mETE was significantly associated with poorer outcome on cancer-specific survival [ 14 ]. Parvathareddy et al analyzed a cohort of 1430 patients and suggested that m-ETE is an independent marker for poor recurrence-free-survival (RFS) [ 15 ]. On the contrary, Nixon et al [ 16 ] studied 984 patients and found no significant difference in 10-year disease-specific survival or RFS between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other factors than mETE can affect DFS and especially the presence of LNI, which is a recognized factor of recurrence [ 19 ]. In his recent study, Parvathareddy et al found that mETE was associated with LNI at the beginning of the disease, but also with distant metastasis [ 15 ]. However, despite the difference in the rate of patients with LNI between the two groups, mETE kept its own prognostic impact on DFS after adjustment on the other prognostic variables, as well as in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrathyroidal extension of thyroid carcinoma has been demonstrated to show an adverse impact on the prognosis of patients [25]. In this study, we first investigated the genes and pathways that dysregulated in invasive thyroid carcinoma based on the data in the TCGA database (thyroid carcinoma samples with extrathyroid carcinoma present extension status ≥ T3).…”
Section: Discussionmentioning
confidence: 99%